Is the smartphone a smart choice? The effect of smartphone separation on executive functions. (November 2016) - Hartanto, Andree; Yang, Hwajin
Abstract: Despite a huge spike in smartphone overuse, the cognitive and emotional consequences of smartphone overuse have rarely been examined empirically. In two studies, we investigated whether separation from a smartphone influences state anxiety and impairs higher-order cognitive processes, such as executive functions. We found that smartphone separation causes heightened anxiety, which in turn mediates the adverse effect of smartphone separation on all core aspects of executive functions, including shifting (Experiment 1) and inhibitory control and working-memory capacity (Experiment 2). Interestingly, impaired mental shifting was evident regardless of the extent of smartphone addiction, whereas smartphone addiction significantly moderated the negative effect of smartphone separation on inhibitory control, as assessed by the Stroop task. The study sheds light on cognitive mechanisms that may underlie some of these negative consequences of smartphone overuse. Highlights: We investigated the effect of smartphone separation on anxiety and executive functions. Smartphone separation induced substantial anxiety. Anxiety mediated the adverse effect of smartphone separation on executive functions. Impaired performance was evident regardless of the extent of smartphone addiction.